Experiences and lessons learned for delivery of micronutrient powders interventions - Reerink, Ietje; Namaste, Sorrel M. L.; Poonawala, Alia; Nyhus Dhillon, Christina; Aburto, Nancy; Chaudhery, Deepika; Hou, Kroeun; Griffiths, Marcia; Haque, Mohammad Raisul; Bonvecchio, Anabelle; Jefferds, Maria Elena; Rawat, Rahul (John Wiley & Sons, 2017)
An effective delivery strategy coupled with relevant social and behaviour change communication (SBCC) have been identified as central to the implementation of micronutrient powders (MNP) interventions, but there has been limited documentation of what works. Under the auspices of “The Micronutrient Powders Consultation: Lessons Learned for Operational Guidance,” three working groups were formed to summarize experiences and lessons across countries regarding MNP interventions for young children. This paper focuses on programmatic experiences related to MNP delivery (models, platforms, and channels), SBCC, and training. Methods included a review of published and grey literature, interviews with key informants, and deliberations throughout the consultation process. We found that most countries distributed MNP free of charge via the health sector, although distribution through other platforms and using subsidized fee for product or mixed payment models have also been used. Community-based distribution channels have generally shown higher coverage and when part of an infant and young child feeding approach, may provide additional benefit given their complementarity. SBCC for MNP has worked best when focused on meeting the MNP behavioural objectives (appropriate use, intake adherence, and related infant and young child feeding behaviours). Programmers have learned that reincorporating SBCC and training throughout the intervention life cycle has allowed for much needed adaptations. Diverse experiences delivering MNP exist, and although no one-size-fits-all approach emerged, well-established delivery platforms, community involvement, and SBCC-centred designs tended to have more success. Much still needs to be learned on MNP delivery, and we propose a set of implementation research questions that require further investigation.